Middle-Power Geoeconomics: Indonesia's Economic Diplomacy in the EV Battery Value Chain between China and the EU - Arkananta, Haider (Politeia : Journal of Public Administration and Political Science and International Relations, 2025)
This article examines Indonesia’s economic diplomacy strategy within the global electric vehicle (EV) battery value chain, with a focus on the country's downstream nickel industrial policy. As the world’s largest nickel producer, Indonesia has leveraged its resource advantage by banning raw nickel exports and promoting domestic value-added production. This policy has attracted significant Chinese investment, particularly from companies such as CATL and Tsingshan, while simultaneously triggering a legal dispute with the European Union (EU) at the World Trade Organization (WTO). Through the conceptual lens of economic diplomacy and geoeconomics, this study analyzes how Indonesia, as a rising middle power, navigates competing interests between China and the EU. Using a qualitative case study method and discourse analysis of policy documents and international reports, the article argues that Indonesia’s industrial policy serves both economic and diplomatic functions. It concludes that Indonesia must enhance its institutional capacity and technological diplomacy to avoid asymmetric dependence and to maintain strategic autonomy in an increasingly polarized global supply chain.